2011
DOI: 10.1007/s11033-011-1244-x
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin regulates mRNA levels of a gene involved in iron utilization in Entamoeba histolytica

Abstract: Entamoeba histolytica is a human pathogen, which can survive using haemoglobin (Hb) as only iron supply. Two probable haemophores (Ehhmbp26 and Ehhmbp45) are involved in iron acquisition in this parasite. However, mechanisms related to their transcriptional regulation have not been studied yet. In the present work, transcriptional profiles of both genes were evaluated in trophozoites cultures grown with different iron sources. ehhmbp26 gene was repressed totally by free iron, whereas ehhmbp45 gene showed clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In all three groups, the viability of the amebae was higher than 80% after 72 h of culture. It is possible that iron differentially modulates virulence in G. duodenalis , as has been reported in E. histolytica [ 18 , 21 , 24 , 25 , 26 ] and T. vaginalis [ 17 , 19 , 20 , 22 , 23 ]. In this study, a marked decrease in parasite viability was observed over long periods of time in media under IR conditions, reflecting the parasite’s need for iron to survive.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In all three groups, the viability of the amebae was higher than 80% after 72 h of culture. It is possible that iron differentially modulates virulence in G. duodenalis , as has been reported in E. histolytica [ 18 , 21 , 24 , 25 , 26 ] and T. vaginalis [ 17 , 19 , 20 , 22 , 23 ]. In this study, a marked decrease in parasite viability was observed over long periods of time in media under IR conditions, reflecting the parasite’s need for iron to survive.…”
Section: Discussionmentioning
confidence: 94%
“…All three genes were negatively regulated by iron, showing overexpression under IR conditions ( Figure 2 A–F). The expression of these three genes was similar to that of the E. histolytica Ehhmbp26 gene [ 24 ], whose RNA sequence formed two IRE-like hairpins at both UTRs. However, the IRE-like structure at the 3′ UTR appeared to be more stable [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Entamoeba histolytica , an enteric protozoan parasite capable of invading the intestinal mucosa and spreading to other organs uses iron as an important factor for growth, adherence, and virulence induction. The iron-dependent differential expression of mRNA encoding a 26 kDa hemoglobin-binding protein ( ehhmbp26 ), a protein involved in iron acquisition, was also reported [ 79 ]. The existence of mRNAs with IRE-like hairpins in this organism is being experimentally analyzed.…”
Section: Iron Homeostasis: Intracelullar Regulation Mediated By Thmentioning
confidence: 99%